2013
DOI: 10.4049/jimmunol.1301482
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 gp120 Induces TLR2- and TLR4-Mediated Innate Immune Activation in Human Female Genital Epithelium

Abstract: Although women constitute half of all HIV-1–infected people worldwide (UNAIDS World AIDS Day Report, 2011), the earliest events in the female reproductive tract (FRT) during heterosexual HIV-1 transmission are poorly understood. Recently, we demonstrated that HIV-1 could directly impair the mucosal epithelial barrier in the FRT. This suggested that the HIV-1 envelope glycoprotein gp120 was being recognized by a membrane receptor on genital epithelial cells, leading to innate immune activation. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 61 publications
2
125
0
3
Order By: Relevance
“…In the case of HIV-1, our group has shown that the Tat protein, in addition to gp120 (52) and Vpr (15), by activating the TLR4 pathway, leads to the production of proinflammatory cytokines, including TNF-␣, IL-1␤, IL-6, IL-8, and type 1 IFN-␣1, and to stimulation of immunosuppressive factors, including IL-10, PD-L1, and IDO, by dendritic cells (22)(23)(24), thus supporting the implication of the HIV-1 Tat protein as a potential pathogenic factor. The product of the tat gene is a protein of 14 to 16 kDa, composed of 86 to 101 amino acids, which is expressed during the early phase of the HIV-1 cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of HIV-1, our group has shown that the Tat protein, in addition to gp120 (52) and Vpr (15), by activating the TLR4 pathway, leads to the production of proinflammatory cytokines, including TNF-␣, IL-1␤, IL-6, IL-8, and type 1 IFN-␣1, and to stimulation of immunosuppressive factors, including IL-10, PD-L1, and IDO, by dendritic cells (22)(23)(24), thus supporting the implication of the HIV-1 Tat protein as a potential pathogenic factor. The product of the tat gene is a protein of 14 to 16 kDa, composed of 86 to 101 amino acids, which is expressed during the early phase of the HIV-1 cycle.…”
Section: Discussionmentioning
confidence: 99%
“…A role for specific glycosylation would be in line with other viral glycoproteins that can activate DC, including the fusion protein of respiratory syncytial virus and HIV-derived gp120 as previously described (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Recent studies have shown that HIV disrupted the epithelial TJ in an intestinal cell line and primary endometrium epithelial cells. 10,35 However, no studies have determined the direct effect of HIV on the epithelium in human ectocervical or colon tissues.…”
Section: Discussionmentioning
confidence: 99%